TRAINING AND COUNSELING ON THE IMPORTANCE OF WORK SAFETY IN BBPLK SERANG CITY - Mamay Komarudin; Wahyu Widodo; Irma Nurmala Dewi (Yayasan Education and Social Center, 2021)
A safe and healthy workplace is what every worker in the company would want. Therefore, it is vital that we lecturers from Bina Bangsa University feel called to hold counselling and training on K3 to prospective workers in Serang City. Counselling and training aim to reduce accidents due to work to improve the efficiency and productivity of work. Companies in Indonesia, in general include common concern about K3 compared to other countries. Indonesia will be difficult to deal with the global market with these conditions because it will experience inefficiencies in labor utilization due to low work productivity. The problems outlined earlier are attempted to be approached using pictures and props. The counseling and training on K3 are expected to reduce the risk of accidents and health problems for prospective workers and the surrounding community.